THE EFFECT OF APPLICATION OF THE POE (PREDICT OBSERVE EXPLAIN) LEARNING MODEL TO INCREASING THE ABILITY OF MASTERING THE SCIENCE CONCEPTS OF JUNIOR HIGH SCHOOL STUDENTS - Salsa Billa Zahra; Monica Prima Sari; Rahmah Evita Putri; Firda Az Zahra (Pendidikan IPA, FMIPA, UNP, 2023)
The learning model is needed so that students can actively research and properly apply the subject matter. POEa is one of them. Utilizing POE as a teaching method can help students learn science. The POE learning model is the subject of this study's literature review. This study tries to ascertain whether educating junior high school students using the POE (Predict, Observe, Explain) paradigm will increase their understanding of scientific concepts. Next, we organize each section by broad topic. Based on selected publications, research data. According to research results, using the POE learning method can improve students' understanding of scientific ideas, help them approach science critically, and improve their academic achievement.